LPN to RN transitions - Claywell, Lora (Mosby, 2003)
Designed to fit LPN to RN transition courses, this practical book helps students succeed both academically and professionally -two distinct, but equally important ways. Unit One focuses on the academic and personal needs of the returning LPNs, helping them assess their past professional and personal accomplishments as well as the goals that they would like to achieve in nursing school. It provides useful tools to help them assess their academic skills, motivational exercises to complete, and resources to use throughout nursing school. Unit Two provides the information students need to bridge the gap between LPN and RN practice, presenting the knowledge and skills they need for the role transition to a RN. It demonstrates the difference between the two levels of practice, and it focuses on the critical thinking, clinical, and communication skills that LPN students need to successfully transition to the RN role.